The Influence Of Transformational Leadership And Secretary Support On Employee Organizational Commitment Through Mediation: Psychological Empowerment And Moderation: Structural Distance On Bintan Regency In The New Normal Era - Rahmawati, Putri; Indrayani, Indrayani; Kaddafi, Muamar (International Journal of Artificial Intelligence Research, 2024)
Organizational commitment is very important for organizations in order to improve organizational performance. Employee organizational commitment can increase or decrease. Knowing the factors that influence organizational commitment is the key to solving the problem of decreasing employee organizational commitment. This research aims to determine the influence of transformational leadership and Secretary support on employee organizational commitment through empowering psychologists as an intervening agent and structural distance as a moderating variable. Data was obtained by distributing questionnaires to 276 civil servants who worked at the Regional Apparatus Organization of Bintan Regency, Riau Islands Province. The research uses a quantitative approach. The data analysis method used is a structural equation model using the Smart-PLS device. The research results show, 1) Transformational leadership and support from the Secretary directly have a positive and significant effect on psychological empowerment. 2) Transformational leadership and psychological empowerment directly have a positive and significant effect on Organizational Commitment, while 3) Secretary Support and Structural Distance do not have a significant effect on organizational commitment. 4) psychological empowerment fully mediates the influence of transformational leadership on organizational commitment, and also mediates the influence of Secretary support on organizational commitment. 5) Structural distance moderates the influence of transformational leadership on employee organizational commitment in the Bintan Regency Regional Apparatus Organization. And also moderates Psychological Empowerment of Organizational Commitment, but does not moderate Secretary Support for Organizational Commitment. The results of this research recommend that practitioners and leaders in the Bintan Regency Regional Apparatus Organization be able to improve transformational leadership competence in inspiring followers, and encourage the Secretary to accommodate opinions from subordinates, include subordinates in the planning process and increase employee organizational commitment.